Brand Image and Satisfaction Drive Repurchase Intentions, While Ambassadors Fail in Indonesia: Citra Merek dan Kepuasan Mendorong Niat Beli Ulang, Sementara Duta Merek Gagal di Indonesia - Iflaahiyah S, Nurul; Komalasari, Dewi (Indonesian Journal of Law and Economics Review, 2024)
This study investigates the impact of Brand Image, Brand Ambassador, and Consumer Satisfaction on repurchase intention for Scarlett Whitening products in Sidoarjo. Using a quantitative approach, data were collected from 96 respondents through questionnaires and analyzed using multiple linear regression with SPSS 16.0. The results show that both Brand Image and Consumer Satisfaction positively and significantly affect repurchase intention, while Brand Ambassador does not. These findings highlight the importance of enhancing brand image and consumer satisfaction to encourage repeat purchases. Companies should prioritize these areas to maintain customer loyalty and drive sales. Highlight: Brand Image: Significantly boosts repurchase intention for Scarlett Whitening products. Consumer Satisfaction: Crucial for encouraging repeat purchases. Brand Ambassador: Does not significantly influence repurchase intention. Keyword: Brand Image, Brand Ambassador, Consumer Satisfaction, Repurchase Intention, Scarlett Whitening